Integration of Wind Connection Low Frequency AC Transmission System using Back to Back Converters - et al., Thimma Reddy (International Journal of Advanced Science and Technology, 2019)
The demand for worldwide electricity is projected to keep growing. As we know that resources are very limited, it is very important to save them for future generation in many aspects. One such limited element is land. We have 1/3 rd of earth is with the land and rest is covered with water. Since we have shortage of space everything cannot be done on the land itself. Now a day in developing countries power is the main demand and generation of power is done in very large scale which needs more land and equipment which leads to high capital investment. Keeping these points in view off shore wind power generation is proposed. By using off shore wind we can generate bulk amount of power generation. But it is facing high economical and technical challenges. The budget for offshore wind power has usually been higher than that of onshore wind generation, but costs have been decreasing quickly in recent years and in Europe has been price economical with conventional power sources since 2017. The common off shore wind farms are grid connected via High Voltage AC (HVAC) transmission, the present researchers and industry experts are concentrating on cost effective transmission alternatives to present technologies. The future of transmission system focuses on finding the alternatives to transmit the maximum power at less cost. A novel Low Frequency AC (LFAC) Transmission System has proposed for transmission of bulk power over long distance (>100kms) by using an intermediate frequency with low investment cost. This manuscript presents the one of the best approach of Low frequency AC transmission system technology interface the wind. The Low Frequency AC transmission system uses a 1/3rdof nominal frequency (20Hz/16.666Hz) than regular frequency (60Hz/50Hz) of main grids. The LFAC transmission was designed with Back-2-BackVSCs are selected as the most appropriate choice due to the technical benefits of Voltage Source Converters (VSC). An analysis to limit the optimum frequency for LFAC determines that between 100 km and 200 km the frequency lies in the range 20-16.67 Hz, showing the potential for LFAC. The design, analysis and voltage control of the B2B converter based offshore wind connected LFAC system is modeled in Simscapein MATLAB.